34 RELATIONSHIP BETWEEN SERUM CAROTENOID CONCENTRATIONS AND FRAILTY, PROBABLE SARCOPENIA, AND PHYSICAL FUNCTION IN THE IRISH LONGITUDINAL STUDY ON AGEING (TILDA). (25th October 2022) - Murphy, C; Duggan, E; Knight, S; Davis, J; Zuniga, RG; Connolly, E; Kenny, RA; McCarthy, S; Romero-Ortuno, R
Abstract: Background: Lutein and zeaxanthin are antioxidant and anti-inflammatory carotenoids derived from foods such as fruit and vegetables. Serum concentrations of Lutein (Ls ) and Zeaxanthin (Zs ) reflect habitual dietary intake. This study examined the cross-sectional and longitudinal relationships between Ls and Zs and frailty, probable sarcopenia, and indices of physical function in TILDA. Methods: The cross-sectional analysis included n =4672 community-dwelling adults aged ≥50 years with Ls and Zs at Wave 1 (2010). For the longitudinal analyses, changes in usual gait speed (at Wave 3, 2014), grip strength (Wave 4, 2016) and Timed Up-and-Go (TUG; Wave 5, 2018), incident probable sarcopenia (defined as grip strength <27 kg in men, <16 kg in women, at Wave 4) and incident frailty (Fried, at Wave 5) were determined. Multivariable linear and logistic regression analyses were adjusted for age, sex, waist circumference, education, malnutrition, smoking, chronic disease, alcohol intake and physical activity. Results: Cross-sectionally, Ls and Zs were positively associated with gait speed (B [95% CI] per 100-nmol/L higher concentration: Ls 0.67 [0.22, 1.12], Zs 1.3 [0.21, 2.48] cm/s) and inversely associated with TUG time (Ls –0.07 [-0.11, –0.02], Zs –0.14 [-0.25, –0.03] s) and with frailty (OR: Ls 0.61 [0.42, 0.87], Zs 0.23 [0.08, 0.68]), all p <0.05), but not with grip strength or probable sarcopenia. Longitudinally, Ls was inversely associated incident frailty (OR 0.85 [0.04, 0.84], p=0.03), whereas Zs was not (0.83 [0.56, 1.23], p=0.36). Neither Ls or Zs were related to changes in physical function measures or incident probable sarcopenia (p>0.05). Conclusion: Cross-sectionally, lower Ls and Zs were independently associated with frailty, slower gait speed and worse TUG performance. However, Wave 1 Ls and Zs were not predictive of changes in these outcomes over 4-8 years of follow up, with the exception of Ls which was inversely associated with incident frailty after 8 years.